2005
DOI: 10.1007/s11136-004-2407-1
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being and community integration among clients of assertive community treatment

Abstract: Three aspects of community integration (i.e., physical, social, and psychological integration) were examined in relation to subjective well-being (SWB) in a sample of 92 persons with psychiatric disabilities receiving services from assertive community treatment (ACT) teams. Although two of the integration variables, namely physical and psychological integration, were related to SWB at the bivariate level, these relationships were not maintained following sequential multiple regression analysis. Findings suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…Research has demonstrated that a supportive social climate is closely related to overall psychological well-being for individuals with SMI (Prince and Gerber 2005), whereas mental health related stigmatization (i.e., isolation, segregation, lack of belonging) increases depressive-anxiety symptoms and negatively influences social outcomes (Segal et al 1980;Markowitz 1998). Assessing the impact of neighborhood social climate on psychiatric distress is particularly important for individuals with SMI who live in supported housing because they often live alone-in some instances, for the first time in their lives .…”
Section: Rationale and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that a supportive social climate is closely related to overall psychological well-being for individuals with SMI (Prince and Gerber 2005), whereas mental health related stigmatization (i.e., isolation, segregation, lack of belonging) increases depressive-anxiety symptoms and negatively influences social outcomes (Segal et al 1980;Markowitz 1998). Assessing the impact of neighborhood social climate on psychiatric distress is particularly important for individuals with SMI who live in supported housing because they often live alone-in some instances, for the first time in their lives .…”
Section: Rationale and Research Questionsmentioning
confidence: 99%
“…The current findings are especially relevant to experiences of psychological integration. Psychological integration has been defined as an individual's sense of community or belonging (Aubry and Myner 1996;Wong and Solomon 2002;Prince and Gerber 2005). The neighborhood social climate mediator that we analyzed in the current study measures perceptions of acceptance, belonging, and tolerance in the neighborhood.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…[2][3][4] Community integration has been linked with the concept of recovery. 2,5,6 The President_s New Freedom Commission on Mental Health highlights objective aspects in its definition of recovery as a Bprocess in which people are able to live, work, learn, and participate fully in their communities.^7 , p.5 Salazar_s 8 community integration framework links community integration with opportunities for increased community presence and participation and well-being and recovery. Whereas the intent of the current study was to examine community integration from the perspectives of young people with mental health difficulties, the researchers were guided by Aubry and Myner_s 9 conceptualization of community integration as they initially formulated study questions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous empirical research suggests that community participation is likely to lead to an increase in sense of community (Chavis, Hogge, McMillan, & Wandersman, 1986;Prince & Gerber, 2005).…”
Section: The Influence Of Sense Of Communitymentioning
confidence: 99%
“…However, it is likely that other factors influence the associations between these variables (McMillan & Chavis, 1990;Prince & Gerber, 2005).…”
Section: The Influence Of Sense Of Communitymentioning
confidence: 99%